Strategic Limitation of Market Accessibility: Search Platform Design and Welfare - Christopher Teh; Chengsi Wang; Makoto Watanabe (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper explores the relationship between market accessibility and various participants' welfare in an intermediated directed-search market. For a general class of meeting technologies, we provide a necessary and sufficient condition under which efficiency requires imperfect accessibility, such that each seller's listing is only observed by some but not all buyers. We show that the platform optimally implements the efficient outcome, but fully extracts surplus from the transactions it intermediates. We also find that in general, buyers prefer to minimize market accessibility, while sellers prefer a weakly greater accessibility level than that which is socially efficient. The efficiency of imperfect accessibility is robust to the introduction of a second chance for unmatched buyers to search.
Keywords: D83; J64; M37; 330; meeting technology; directed search; platform; intermediation; accessibility